Oxidation of Histidine by Pyridinium Bromochromate in Aquo-Acetic Acid Medium: A Kinetic Investigation - HIRAN, B.L.; MALKANI, R.K.; JAIN, SAPANA (Asian Journal of Chemistry, 2010)
Amino acids do not react with CrO3 and K2Cr2O7 but react with pyridinium bromochromate. Oxidation of histidine with pyridinium bromochromate (PBC) has been studied in 30% acetic acid-70% water (v/v) mixture containing perchloric acid and leads to 2-imidazole aldehyde, carbon dioxide and ammonia as products. The reaction rate is first order with respect to each in [histidine] and [PBC] while inverse second order with respect to [H+]. Michaelis-Menten type kinetics is observed with respect to histidine. The rate of reaction increases with decrease in polarity of solvent indicating ion-dipole interaction. Absence of primary kinetic isotope effect (kH/kD) = 1.12 at 303 K) rules out the α-C-H bond fission in the rate determining step. Activation parameters have been evaluated. A rate limiting C-C bond fission of the chromic-ester formed by zwitter ion of histidine and unprotonated PBC is consistent with the observed results. The rate law proposed and derived is in agreement with experimental results.